Work-family conflict is a public health concern - Kelly D. Chandler (Elsevier, 2021)
Objectives: The objective of this commentary is to describe how the deleterious health effects of the competing demands of work and family roles are a public health issue that deserves immediate attention. Study design: This is a commentary article; therefore, there is no study design. Method: I reviewed and summarized existing research on work-family conflict as it relates to public health action. Results: Work-to-family conflict (WFC) is pervasive among US working adults and is higher in the US than in other developed countries. Time, energy, and behaviors invested in fulfilling work responsibilities often compete with fulfilling family responsibilities, with numerous deleterious effects on employee health including sleep, cardiometabolic risk, stress, depression, and anxiety. WFC is a potent source of stress for working Americans, a major contributor to healthcare costs, and a predictor of mortality. US policies have lagged woefully behind the increasing competition between work and family demands. Conclusion: Work-to-family conflict is a public health concern that deserves immediate attention. Until governmental support for adults' work and family lives improves, WFC will continue to be a significant risk factor for public health. Including WFC in public health research and interventions will improve population health and advance health equity.